Talent Management: Maintaining High Performance Personnel Based on Compatible Competence and Adaptable Culture (Compact) In an Organization - Sugiyono; Suharnomo (International Journal of Psychosocial Rehabilitation, 2020)
For an organization, the existence of talented employees as part of an investment must be well maintained. "War for Talent" becomes a threat demanding an organization to implement a strategy to maintain the talented employees, one of which is called compatible competence and adaptable culture (COMPACT) approach. The aim of this study was to analyze the effect of transformational leadership and adaptability on retention through COMPACT. This research was conducted at a vocational school in Central Java Indonesia as the respondent was the principal, 200 deputy principals, taking data by sending a questionnaire with Google quest sent via WhatsApp, or sent directly to the respondent concerned. The findings of this study indicate that overall exogenous variables have a significant positive effect on endogen variables.